Envers un repertori conceptual de la poesia de Narcís Vinyoles. - ALMENAR, SALVADOR CUENCA (Scripta, 2013)
Narcís Vinyoles's poetry can be depicted by its formal and thematic syncretism, representative of Valencia at the turn of the 15th and 16th centuries, an eclectic city where diverse influences inextricably merged. In this receiving place Vinyoles built up his works with three languages, namely, Catalan, Castilian and Italian, and with different thematic inspirations. Thematically speaking, philosophical concepts are one of the elements mingled by the Valencian poet. In this paper I will only detect these concepts and specify the use made by Vinyoles without the explanation. The repertoire will be divided in five parts, according to the discipline to which concepts belong: epistemology, philosophy of nature, metaphysics, moral philosophy and theology.